Revealing antimicrobial resistance in stormwater with MinION - Białasek, Maciej; Miłobędzka, Aleksandra (Chemosphere, 2020)
Discharge of urban stormwater containing organic matter, heavy metals and sometime human feces, to the natural aquatic reservoirs without any treatment is not only an environmental problem. It can lead to prevalence of antibiotic resistant bacteria in stormwater systems and transmission of antibiotic resistance genes to the environment. We performed antibiotic resistome identification and virus detection in stormwater samples from Stockholm, using publicly available metagenomic sequencing MinION data. A MinION platform offers low-cost, precise environmental metagenomics analysis. 37 groups of antibiotic resistant bacteria (ARB), 11 resistance types with 26 resistance mechanisms - antibiotic resistance genes (ARGs) giving tolerance to the aminoglycoside, beta-lactams, fosmidomycin, MLS, multidrug and vancomycin were identified using ARGpore pipeline. The majority of the identified bacteria species were related to the natural environment such as soil and were not dangerous to human. Alarmingly, human pathogenic bacteria carrying resistance to antibiotics currently used against them (Bordetella resistant to macrolides and multidrug resistant Propionibacterium avidum) were also found in the samples. Most abundant viruses identified belonged to Caudovirales and Herpesvirales and they were not carrying ARGs. Unlike the virome, resistome and ARB were not unique for stormwater sampling points. This results underline the need for extensive monitoring of the microbial community structure in the urban stormwater systems to assess antimicrobial resistance spread.
Keywords: metagenom; feces; Feces; Wastewater; monitorování životního prostředí; Macrolides; bakteriální geny; lidé; makrolidy; ARB; Microbiota; ARG; metagenomika; bakteriální léková rezistence; odpadní voda; Metagenome; mikrobiota; beta-laktamy; Metagenomics; Bacteria; beta-Lactams; Environmental Monitoring; Waste Water; MinION; Genes, Bacterial; Drug Resistance, Bacterial; Stormwater; Humans